Interference Cancellation Schemes for Single-Carrier Block Transmission with Insufficient Cyclic Prefix. (17th October 2007) - Hayashi, Kazunori; Sakai, Hideaki
Abstract : This paper proposes intersymbol interference (ISI) and interblock interference (IBI) cancellation schemes at the transmitter and the receiver for the single-carrier block transmission with insufficient cyclic prefix (CP). The proposed scheme at the transmitter can exterminate the interferences by only setting some signals in the transmitted signal block to be the same as those of the previous transmitted signal block. On the other hand, the proposed schemes at the receiver can cancel the interferences without any change in the transmitted signals compared to the conventional method. The IBI components are reduced by using previously detected data signals, while for the ISI cancellation, we firstly change the defective channel matrix into a circulant matrix by using the tentative decisions, which are obtained by our newly derived frequency domain equalization (FDE), and then the conventional FDE is performed to compensate the ISI. Moreover, we propose a pilot signal configuration, which enables us to estimate a channel impulse response whose order is greater than the guard interval (GI). Computer simulations show that the proposed interference cancellation schemes can significantly improve bit error rate (BER) performance, and the validity of the proposed channel estimation scheme is also demonstrated.